The Role of Profits Management Practices on Financial Performance in Institutions : an Analytical Study on the Iraqi Stock Exchange for the Period 2013-2022 - Ghufran Shallal Mohammed; Muaamal Hussein Jwesim; Abdelmoneem Ltaif (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The research aimed to determine whether practicing the phenomenon of profits management affects the capital structure of the companies in the research sample. The research population consisted of all companies listed on the Iraq Stock Exchange for the period (2013 - 2022). The research sample included (26) companies that met the conditions. Companies. Among the most important results: (53%) of the companies in the research sample practiced profits management throughout the research period (2013 - 2022), while the remaining companies practiced it for varying periods. It was found that half of the companies in the research sample had lower costs than the general average weighted cost of the capital structure, and recorded the highest costs in the agricultural sector, and the lowest costs in the industrial sector. Among the most important suggestions: Corporate management should be aware of the risks that may result when practicing profits management on the performance and market value of the company.